Utilization And Development of Display Teaching Materials - Sakinah, Nurul; Rahmatika, Aghisna; Widna, Widna; Putri, Alifah Fatria; Khairunnisa, Akma; Gadafi, Khalib; Sobri, Sobri; Efendi, Efendi (Khalaqa: Journal of Education and Learning, 2025)
Display teaching materials are one of the learning media used to present material in visual form to make it easier for students to understand. Types of display teaching materials include images, diagrams, graphs, posters, photographs, realia, and dioramas, each of which plays a role in clarifying learning concepts. Their use can increase students' interest in learning, memory, and the effectiveness of student understanding of the material being taught. In its application, display teaching materials have advantages, such as being able to attract students' attention, simplify complex information, and can be used as an aid in various subjects. However, there are also disadvantages, such as limited size, less interactive than digital media, and the need for creativity in their development to be effective in supporting the learning process. Therefore, the right strategy is needed in selecting and developing display teaching materials to suit students' needs and learning objectives.